Automated Synthesis of Well‐Defined Polymers and Biohybrids by Atom Transfer Radical Polymerization Using a DNA Synthesizer. Issue 10 (6th February 2017) - Pan, Xiangcheng; Lathwal, Sushil; Mack, Stephanie; Yan, Jiajun; Das, Subha R.; Matyjaszewski, Krzysztof
Abstract: A DNA synthesizer was successfully employed for preparation of well‐defined polymers by atom transfer radical polymerization (ATRP), in a technique termed AutoATRP. This method provides well‐defined homopolymers, diblock copolymers, and biohybrids under automated photomediated ATRP conditions. PhotoATRP was selected over other ATRP methods because of mild reaction conditions, ambient temperature, tolerance to oxygen, and no need to introduce reducing agents or radical initiators. Both acrylate and methacrylate monomers were successfully polymerized with excellent control in the DNA synthesizer. Diblock copolymers were synthesized with different targeted degrees of polymerization and with high retention of chain‐end functionality. Both hydrophobic and hydrophilic monomers were grafted from DNA. The DNA‐polymer hybrids were characterized by SEC and DLS. The AutoATRP method provides an efficient route to prepare a range of different polymeric materials, especially polymer‐biohybrids. Abstract : Autorad : Photoinduced atom transfer radical polymerization is conducted in an automated DNA synthesizer to prepare well‐defined homopolymers, diblock copolymers, and biohybrids. This technique provides a clean polymerization system under ambient temperature with oxygen tolerance.